Social Assessment - McPhail, Kathryn; Jacobs, Sue (World Bank, Washington, DC, 2012)
Social assessment (SA) provides a framework for incorporating participation and social analysis into the design and delivery of Bank-assisted operations. Since there are many social variables which potentially affect project impacts and success, SAs must be selective and strategic, and focus on issues of operational relevance. Prioritizing critical issues, and determining how to address them, requires consultation with stakeholders, and other forms of data collection and analysis. SAs are carried out in a project context in order to: (a) identify key stakeholders and establish an appropriate framework for their participation in project selection, design, implementation, and monitoring, and evaluation; (b) ensure that project objectives and incentives for change are acceptable to the range of people intended to benefit, and that gender, ethnicity and other social differences are taken into account in project design; (c) assess the social impact of investment projects, and where adverse impacts are identified, determine how they can be avoided, minimized, or substantially mitigated; and (d) develop the capacity to enable participation, resolve conflict, permit service delivery, and carry out mitigation measures in ways that are socially sound.